2016
DOI: 10.1136/jclinpath-2016-203639
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction induces atrial inflammation that can be prevented by C1-esterase inhibitor

Abstract: MI induces atrial inflammation in patients and in rats. C1inh treatment could counteract this MI-induced atrial inflammation in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…More recently, IC1 treatment has also been postulated to counteract myocardial infarction-induced inflammation in a rat model. 36 These data are consistent with our findings of increased IC1 levels among CS survivors. In another line of evidence, it has been reported that patients with more severe forms of septic shock could exhibit a relative deficiency of IC1, 37 also in agreement with our findings in patients with CS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More recently, IC1 treatment has also been postulated to counteract myocardial infarction-induced inflammation in a rat model. 36 These data are consistent with our findings of increased IC1 levels among CS survivors. In another line of evidence, it has been reported that patients with more severe forms of septic shock could exhibit a relative deficiency of IC1, 37 also in agreement with our findings in patients with CS.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, these four proteins reflect multiorgan dysfunction, as well as systemic inflammation and immune activation. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] During the early hours of CS, changes in the expression of these proteins may precede overt multiorgan failure and identify patients at a higher mortality risk. These data highlight the relevance of systemic involvement in CS, beyond primary pump failure.…”
Section: Discussionmentioning
confidence: 99%
“…In animal model, prolonged P-wave duration was related to abnormal inter-atrial conduction, independent of the left atrium size, mediated by dysregulation of connexin proteins expression (CX 40 and CX 43) and fibrosis[ 12 ]. In patients with acute coronary syndromes, it has been found an increased number of inflammatory cells infiltrate the atria, coming from the adipose tissue, suggesting that the left ventricular infarction induces atrial inflammation [ 22 ]. By inference, it is possible that the prolonged P-wave represents an early sign of chronic or acute inflammatory stimuli on atrial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, C1-INH exhibited therapeutic effects in other diseases and clinical situations [25,24] and may have therapeutic potential in numerous diseases, where the tightly cross-linked complement and contact system are concurrently activated [2]. Due to their C1-INH potentiating effect, sulfated glycans may offer an option to improve either the efficacy of therapeutically applied C1-INH or the activity of endogenous C1-INH.…”
Section: Discussionmentioning
confidence: 99%
“…These may also be obstacles to the application of C1-INH in further indications, although clinical studies showed beneficial effects of C1-INH also in other disease states like sepsis, gram-negative endotoxic shock, vascular leak syndrome, transplant rejection, ischemia-reperfusion injury, myocardial infarction, and emergency coronary artery bypass surgery [24,25]. …”
Section: Introductionmentioning
confidence: 99%